Nonlinearities in Drug Release Process from Polymeric Microparticles: Long-Time-Scale Behaviour - Elena Simona Bacaita; Costica Bejinariu; Borsos Zoltan; Catalina Peptu; Gabriela Andrei; Marcel Popa; Daniela Magop; Maricel Agop (Journal of Applied Mathematics)
A theoretical model of the drug release process from polymeric microparticles (a particular type of polymer matrix), through dispersive fractal approximation of motion, is built. As a result, the drug release process takes place through cnoidal oscillations modes of a normalized concentration field. This indicates that, in the case of long-time-scale evolutions, the drug particles assemble in a lattice of nonlinear oscillators occur macroscopically, through variations of drug concentration. The model is validated by experimental results.